"Callous‐unemotional" conduct disorder subgroup: Difficult to treat. Issue 3 (March 2015) - Knopf, Alison
<x xml:space="preserve">Abstract</x> Conduct disorder in youth is associated with an increased risk for substance abuse, criminal behavior, and school problems; it also creates suffering and financial costs. A review from the National Institute of Mental Health (NIMH) summarizes current data and looks at promising areas for research. Because treatment is usually focused on symptoms and not underlying problems, the researchers also highlighted treatments. The focus is on two subgroups of conduct disorder — youths who are "callous‐unemotional" and youths who are not.